The fracture energy (G F) of high-strength concretes - Giaccio, Graciela Marta (1993)
This paper presents results for the fracture energy of concrete (GF) obtained from a wide range of high-strength concretes. Strength levels up to 100 MPa, aggregate type and aggregate surface texture were included as variables. The determination ofGF was performed according to the recommendation of the RILEM 50-FMC Committee. Compressive and tensile strengths and the modulus of elasticity are also presented. Measured values of GF are compared with those proposed in the last CEB Model Code.